C15-bacillomycin D produced by Bacillus amyloliquefaciens 4-9-2 suppress Fusarium graminearum infection and mycotoxin biosynthesis - Liu, Zhongliang; Luo, Yijia; Lin, Rongxin; Li, Chengming; Zhao, Hanjun; Aman, Haqmal Mohammad; Wisal, Muhammad Asif; Dong, Huifeng; Liu, Dingkuo; Yu, Xiaona; Kong, Lingcong; Ma, Hongxia (Frontiers in Microbiology, 2025)
IntroductionFusarium graminearum threatens global food security through crop diseases and mycotoxin contamination, presenting significant challenges in controlling this toxigenic pathogen.MethodsSoil bacteria were isolated and screened for antagonism using plate confrontation. Active strain 4-9-2 was identified by 16S rDNA and whole-genome sequencing. Antifungal metabolites were characterized via AntiSMASH, HPLC, and ESI-IT-TOF/MS. MIC and IC₅₀ against F. graminearum spores/hyphae were determined. Biocontrol efficacy was tested on maize kernels, measuring infection suppression and mycotoxin reduction. Compound stability was assessed under varying temperatures (25–100°C), pH (2–12), metal ions, and enzymes. Mechanisms were investigated through microscopy, membrane permeability, ROS, and membrane potential assays.ResultsStrain 4-9-2 (Bacillus amyloliquefaciens) showed potent antifungal activity. Its genome (3,957,046 bp, GC 46.5%) harbored 12 BGCs. The metabolite was identified as C15-bacillomycin D, inhibiting F. graminearum at MIC 64 μg/mL and IC50 26.10 μg/mL. It suppressed maize kernel infection and reduced deoxynivalenol (DON) and zearalenone (ZEN) levels. Bacillomycin D maintained activity across tested temperatures, pH, and stressors. It disrupted membrane integrity, causing morphological defects, increased permeability, ROS accumulation, and membrane depolarization.DiscussionBacillomycin D from B. amyloliquefaciens 4-9-2 is a promising biocontrol agent against F. graminearum, combining potent antifungal activity, mycotoxin reduction, environmental resilience, and membrane-targeting action.